2019
DOI: 10.1021/acs.est.9b02963
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A, Chlorinated Derivatives of Bisphenol A and Occurrence of Myocardial Infarction in Patients with Type 2 Diabetes: Nested Case-Control Studies in Two European Cohorts

Abstract: A positive association between Bisphenol A (BPA) exposure and coronary heart disease has been shown, but not in patients with type 2 diabetes (T2D). During the treatment of drinking water, chlorination leads to the formation of chlorinated derivatives of Bisphenol A (ClxBPA), that have higher estrogenic activity than BPA. No evidence exists for a relationship between exposure to ClxBPA and myocardial infarction in patients with T2D. The objective of this study was to evaluate the relationship between exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 45 publications
(67 reference statements)
0
13
1
Order By: Relevance
“…Previous studies have reported that urinary BPA is positively associated with an increased prevalence of total CVD in the U.S. population (Cai et al 2020;Hu et al 2019). Another study has shown a positively association between BPA and CVD (Melzer et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that urinary BPA is positively associated with an increased prevalence of total CVD in the U.S. population (Cai et al 2020;Hu et al 2019). Another study has shown a positively association between BPA and CVD (Melzer et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Several epidemiological investigations have been developed to assess the cardiotoxic effects of BPA. The evidence is consistent, reporting that there is an association between exposure to BPA and an increased prevalence of CVDs [ 103 , 104 ] including atherosclerosis [ 105 ], coronary artery disease (CAD) [ 104 , 106 , 107 , 108 , 109 ], peripheral artery disease (PAD) [ 110 ], dilated cardiomyopathy (DCM) [ 109 ], and myocardial infarction (MI) [ 104 , 111 ]; heart failure; and angina pectoris [ 104 ] and its risk factors, such as hypertension [ 112 , 113 , 114 , 115 ] and diabetes [ 103 , 108 ] ( Figure 2 ). There is a multiplicity of different analytical techniques to quantify BPA concentrations in human tissues.…”
Section: Effects Of Bpa On Humansmentioning
confidence: 99%
“…The authors demonstrated the exposure to BPA in the two studies (ESTHER cohort: 31% and SURDIAGENE cohort: 38%). The meta-analysis of the results showed that in booth cohorts, there exists a positive association between MI and the detection of BPA in urine (OR = 1.97; 95% CI = 1.05–3.70, p = 0.04) [ 111 ]. More recently, in 2020, Cai et al evaluated the relationship between urinary BPA levels and CVDs in the U.S. adult population using data from NHANES 2003–2014.…”
Section: Effects Of Bpa On Humansmentioning
confidence: 99%
“…Therefore, BPA affects estrogen receptor functions and also other nuclear hormone receptors (Fenichel et al, 2013). In recent years, exposure to BPA has been associated with a wide range of metabolic, reproductive, cardiovascular and neurological diseases and also with increased incidences of endocrine diseases and endocrine-related cancers (Dunder et al, 2019;Friques et al, 2020;Hafezi and Abdel-Rahman, 2019;Hu et al, 2019;Khan et al, 2019;Piao et al, 2019;Santoro et al, 2019;Shu et al, 2019;Win-Shwe et al, 2019). These effects are mediated by hormonal regulation and metabolic signals, mainly by nuclear receptors, or by mechanisms that are currently unknown.…”
Section: Introductionmentioning
confidence: 99%